Kakim vremenem predpočtitel’nee perevodit’ posylki zakonodatel’nych položenij zakonov Chammurapi? - Kaplan, Golda Ch.
Resümee: Which Tense is Preferable for Translating Premises of the Law Clauses in the Code of Hammurapi?